2018
DOI: 10.1590/s0100-204x2018000200004
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-anatomical and physiological alterations of passion fruit fertilized with silicone

Abstract: The objective of this work was to evaluate the effect of silicon fertilization on gas exchange, leaf anatomy, and ultrastructural characteristics of passion fruit (Passiflora edulis). The treatments comprised four concentrations of silicon (0, 0.28, 0.55, and 0.83 g per pot) at 1% silicic acid solution (SiO2.XH2O). This solution was applied around the stems of the plants. The first application was made 15 days after seedlings were transplanted. In total, three applications were made at 15-day intervals. The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…Also, we have recently demonstrated that TiO 2 NPs (anatase: rutile) are chronically applied to T. aestivum, decreased maximal and effective efficiency of PSII, net photosynthetic rate, transpiration rate, stomatal conductance, intercellular CO 2 concentration, and starch content (Dias et al 2019). On the other hand, the application of SiO 2 NPs improves the gas exchange performance in Passiflora edulis with an increase of Pn, E, and gs (Costa et al 2018). Overall, our data suggest that low doses of TiSiO 4 NPs play some protective role in photosystem II, not having the negative impacts of TiO 2 NPs.…”
Section: Discussionmentioning
confidence: 55%
“…Also, we have recently demonstrated that TiO 2 NPs (anatase: rutile) are chronically applied to T. aestivum, decreased maximal and effective efficiency of PSII, net photosynthetic rate, transpiration rate, stomatal conductance, intercellular CO 2 concentration, and starch content (Dias et al 2019). On the other hand, the application of SiO 2 NPs improves the gas exchange performance in Passiflora edulis with an increase of Pn, E, and gs (Costa et al 2018). Overall, our data suggest that low doses of TiSiO 4 NPs play some protective role in photosystem II, not having the negative impacts of TiO 2 NPs.…”
Section: Discussionmentioning
confidence: 55%
“…O aumento deve-se, principalmente, à camada de cera epicuticular mais desenvolvida, que promove processo importante para prevenir ações de patogênese viral como a germinação e penetração de fungos. Deposições de silício, também, foram observadas em folhas de maracujá que receberam adubações com o elemento (Costa et al, 2018). Figura 2.…”
Section: Tratamentosunclassified
“…O tomateiro é uma das hortaliças mais cultivadas e consumidas no mundo. O grupo cereja constitui-se como um tomate para mesa com crescente aumento no seu consumo in natura (Costa et al, 2018). Possui tamanho pequeno, forma arredondada ou alongada e cor vermelho-brilhante, lembrando uma cereja (Rodrigues et al, 2016).…”
Section: Introductionunclassified
“…The application of Si has beneficial effects on many fruit crops, but there is still little information about the effect of Si on blueberry. The application of Si in passion fruit (Passiflora edulis) increased the photosynthetic rate of the plant (Costa et al, 2018), and in strawberry (Fragaria × ananassa) its improved pulp firmness and increased the level of anthocyanins in fruits (Munaretto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%